2022
DOI: 10.1101/2022.03.10.483848
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of Morreton Virus (MORV) as a Novel Oncolytic Virotherapy Platform for Liver Cancers

Abstract: Morreton virus (MORV) is a novel oncolytic Vesiculovirus, genetically distinct from vesicular stomatitis virus (VSV). we report that MORV induced potent cytopathic effects in a panel of cholangiocarcinoma (CCA) and hepatocellular carcinoma (HCC) cell lines. In addition, high intranasal doses of MORV were not associated with significant adverse effects and were well tolerated in mice bearing liver tumor xenografts and syngeneic liver cancers. Furthermore, single intratumoral treatments with MORV (1 x 107 TCID50… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…We have previously shown that responsiveness to I IFN production or viral kinetic in vitro by infected cancer cell lines does not always correlate with in vivo efficacy to oncolytic. 4 To determine whether JURV can induce an oncolysis-dependent tumor growth delay, we injected IT three doses of JURV into the immunocompromised HEP3B-xenografts. We employed luciferase tagged HEP3B cells to monitor tumor growth during the first three weeks of treatment.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that responsiveness to I IFN production or viral kinetic in vitro by infected cancer cell lines does not always correlate with in vivo efficacy to oncolytic. 4 To determine whether JURV can induce an oncolysis-dependent tumor growth delay, we injected IT three doses of JURV into the immunocompromised HEP3B-xenografts. We employed luciferase tagged HEP3B cells to monitor tumor growth during the first three weeks of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Rhabdoviruses possess several advantageous properties over other oncolytic viral vector platforms, including amenability to genetic manipulation, and not using humans as a natural host resulting in low seroprevalence in the population. 5 In addition to an episomal 85 and fast kinetic cycle in tumor cells, most vesiculoviruses can encode large transgenes 4 while maintaining the ability to potently infect, replicate and induce apoptosis 86,87 in a vast array of cancer cells. [88][89][90][91][92][93][94] We and others have shown that others non-vesicular stomatitis virus (VSV) members 4,95 of the Rhabdoviridae family have tremendous potential as oncolytic agents because of their natural tumor selectivity and hypersensitivity to type 1 interferon response which is defective in 80% of tumors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations